Accurate Localization of the Integration Sites of Two Genomic Islands at Single-Nucleotide Resolution in the Genome of Bacillus cereus ATCC 10987. (10th February 2008) - Zhang, Ren; Zhang, Chun-Ting
Abstract : We have identified two genomic islands, that is, BCEGI-1 and BCEGI-2, in the genome of Bacillus cereus ATCC 10987, based on comparative analysis with Bacillus cereus ATCC 14579. Furthermore, by using the cumulative GC profile and performing homology searches between the two genomes, the integration sites of the two genomic islands were determined at single-nucleotide resolution. BCEGI-1 is integrated between 159705 bp and 198000 bp, whereas BCEGI-2 is integrated between the end of ORF BCE4594 and the start of the intergenic sequence immediately following BCE4626, that is, from 4256803 bp to 4285534 bp. BCEGI-1 harbors two bacterial Tn7 transposons, which have two sets of genes encoding TnsA, B, C, and D. It is generally believed that unlike the TnsABC+E pathway, the TnsABC+D pathway would only promote vertical transmission to daughter cells. The evidence presented in this paper, however, suggests a role of the TnsABC+D pathway in the horizontal transfer of some genomic islands.